1998
DOI: 10.1007/s004180050234
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of IFN-γ, IL-4, IL-10, and IL-1β mRNAs in decalcified tissue sections of mouse lipopolysaccharide-induced periodontitis mandibles assessed by in situ hybridization

Abstract: To examine the role of T cell subgroups, Th1 and Th2, in the development of periodontitis, the expression of various cytokines was investigated in a mouse model of alveolar bone resorption using in situ hybridization (ISH) with digoxigenin-labeled oligonucleotides. When mice received repetitive injections with Escherichia coli lipopolysaccharide into the gingiva every 48 h, alveolar bone resorption was detectable after the fourth injection, reaching a maximum after the 13th injection. For the best performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Seymour et al [25] and Gemmell et al [26] proposed that the progression of periodontal diseases is characterized by a shift from a predominantly Th1 to a Th2 cell profile. This hypothesis is supported by some studies [2, 7, 11, 27, 28, 29, 30, 31] but has not been confirmed by others [32, 33]. Ellis et al [10] suggested that progressively lower gingival concentrations of IL-12 and higher IL-6 concentrations associated with increasing sulcular depth not only indicates a shift from a Th1 to a Th2 immunologic phenotype, but also suggests a regulatory role for IL-12 in that shift.…”
Section: Discussionsupporting
confidence: 70%
“…Seymour et al [25] and Gemmell et al [26] proposed that the progression of periodontal diseases is characterized by a shift from a predominantly Th1 to a Th2 cell profile. This hypothesis is supported by some studies [2, 7, 11, 27, 28, 29, 30, 31] but has not been confirmed by others [32, 33]. Ellis et al [10] suggested that progressively lower gingival concentrations of IL-12 and higher IL-6 concentrations associated with increasing sulcular depth not only indicates a shift from a Th1 to a Th2 immunologic phenotype, but also suggests a regulatory role for IL-12 in that shift.…”
Section: Discussionsupporting
confidence: 70%
“…Actually, the EDTA-based solutions have been used for the purpose of decalcification of tissues for ISH in many recent studies (Fujii et al 1999;Iwasaki et al 1998), while Morse's solution was utilized by Nomura et al (1993) for detection of OC mRNA in odontoblasts. In our case, the latter solution completed decalcification within 24 h, while the former solution needed 7-8 days to decalcify similar samples.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report also showed that subchronic LPS injections (20 injections of 5 g at 48-h intervals) into gingiva of mice produced a maximum level of interferon-␥ (INF-␥ ) (a Th1 cytokine) at the tenth injection but that INF-␥ decreased thereafter. IL-4 (a Th2 cytokine) began to increase after the tenth injection (31). Based on these find- Figure 1.…”
Section: Effect Of Home Endotoxin Exposure On Wheeze In the First Yeamentioning
confidence: 92%